(3EWdGdGJ Ydi GdRef GdBJis - (3GdSjO, GdSjO fUQ GdOjfs ((3GdbGgQIs (3GdgjFI GdeUQjI GdYGeI ddcJGHs, 1996)
(3jWQM GdcJGH YOI ehVhYGJ efgG eaghe GdSjHQfWjbG MVGQI GdCda GdKGdKI hGdCejI GdJcfhdhLjI heG jUGMHgG ef TYhQ HGdGZJQGH GdJcfhdhLi ceG jVY GdcJGH JSGDdGJ Mhd WHjYI GdJcfhdhLjG GdMGceI ai GdbQf GdhGMO hGdYTQjfs
(3GdeMJhjGJ (B: (3HhQJhQjg ddRef GdBJi(B--(3gehe eUQjI(B--(3CMGOjK Mhd eSJbHd GdKbGaI ai eUQ(B--(3CMhGd Ybd GdCeI(B--(3ef CHLOjGJ acQ GdfgVIs
(3jTJed Ydi bGFeI HYfhGf GbQC ai gPg GdSdSdIs
Hurg
5 14
Keywords: (3GdJcfhdhLjG hGdMVGQIs; (3GdJcfhdhLjGs -- (3GdLhGfH GdELJeGYjIs; (3GdJcfhdhLjGs -- (3NOeGJ GdeYdheGJs; (3GdJcfhdhLjGs; (3GdMVGQI GdMOjKIs; (3GdSjHQGfJjcs; (3fXe GdeYdheGJs